USING THE PEARL AND THE SEA WOLF IN EFL CLASS: ENHANCING LANGUAGE, CULTURE, AND ENVIRONMENTAL LITERACY FOR BLUE ECONOMY - Dewi, Novita; Sulistiyowati, Firma; Castro, Maria Corazon Saturnina Aspeli (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
This research explores the use of American classic novels in EFL teaching to promote sustainable practices in Indonesia’s blue economy, which refers to the utilization of oceanic resources for economic growth while protecting the ocean ecosystem. It proposes The Pearl written in 1947 by John Steinbeck and The Sea Wolf in 1904 by Jack London to enhance communication skills, cultural understanding, and ecological literacy among EFL learners. The study applies a close reading of the literary texts to compare with the context of Indonesia’s marine economy. Class exercises and activities are constructed based on the two novels to boost EFL learners’ language ability while preparing them to become a generation committed to marine sustainability. While The Pearl is a metaphor of human greed, The Sea Wolf symbolizes the danger of exploitation. The aesthetic value of both novels can enhance EFL learners’ critical thinking and ecological awareness. Incorporating ecological perspectives into EFL instruction via maritime literature helps students build the skills and mindset needed to support long-term development in Indonesia’s blue economy. The article suggests that using more maritime narratives into EFL teaching can help improve linguistic proficiency, cultural sensitivity, and environmental consciousness, preparing students for sustainable development.